Penentuan Pola Kalimat Bahasa Inggris Pada Simple Present Tense Menggunakan Metode Bottom Up Parsing - Meilani, Budanis Dwi; Nasir, Muhamad (INTEGER: Journal of Information Technology, 2016)
English is a language widely used by many countries in the world. It has many grammar rules in whichÂ  each has structural pattern regulating composition of clause, phrase, and words in natural language. Simple Present Tense is one of 16 tenses in English Grammar. It is the first and basic tense which used to express regular and habitual action. Most JuniorÂ  High School students have difficulty in determining grammar pattern of tenses, particularly in Simple Present Tense. This research discussed about an application for determining English sentence pattern of Simple Present Tense by using Bottom Up Parsing Method. This is one of Parsing methods used for unscrambling sentence. The English sentence was broken down and translated into pattern forms. The constructed form had rule-base character and implemented Context Free Grammar (CFG). Among 110 inputs of testing, the usage of Bottom Up Parsing Method in determining a sentence pattern got 88.1% data accuracy. In this case, the system could not detect the name of person in interrogative sentence which located at the second word functioning as a subject.